Permainan Kartu (Card Game) Untuk Menghafal Perkalian Melalui Bimbingan Belajar Gratis Pada Usia Sekolah Dasar di Desa Kunci - Safitri, Dian Nurul; Sujiran, Sujiran; Junarti, Junarti; Suriyah, Puput (BAGIMU NEGERI : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2017)
One of the mathematics material that elementary school teaches is multiplication. One of the problems in the Kunci village is that there are still many elementary school students who do not understand or canât memorize multiplication, while in school it is not possible to always multiply because of time and curriculum issues, so additional learning guidance using card game is needed. The result of community service activities is the ability of children in multiplication to increase. As many as 35 of the 40 children or 81,4% children get a score above the average in multiplication tests.Keywords: Card game, multiplication